Adaptation of Meta-Cognitive Awareness Inventory in Physics (MAIP) for Public and Private Senior Secondary School Nigerian Students - Ellah Barnabas; Sunday Oche Emaikwu (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: The study focused on the adaptation of the Meta-Cognitive Awareness Inventory in Physics (MAIP) for senior secondary school students in Nigeria, both in public and private schools. Methodology: The study employed an adaptation research design. The sample included 1,382 SSII students who had taken Physics as a subject. To ensure its validity, the MAIP underwent face validation by five experts. Construct validation of the MAIP was conducted using factor analysis. This involved applying the principal component analysis extraction method and the Varimax rotation method with Kaiser Normalization. Items with a factor loading of 0.40 or higher on any of the factors were selected to be included in the instrument. The coefficient of internal consistency was calculated using Cronbach's Alpha and was found to be 0.78. Research question 1 was addressed through factor analysis, while research question 2 was answered by calculating the coefficient of internal consistency using Cronbach's Alpha. Research question 3 was answered by calculating means and standard deviations. The null hypothesis was tested using an independent t-test at a significance level of 0.05. Findings: The findings of the study revealed that the MAIP consisted of 52 factorially simple or pure items and 23 factorially complex items based on their factor loadings. Significance: The coefficient of internal consistency for the MAIP was found to be 0.98. Furthermore, a statistically significant difference in the mean meta-cognitive awareness ratings was observed between students in private and public schools, favoring students in private senior secondary schools when using the MAIP.